Defect in cooperativity in insulin receptors from a patient with a congenital form of extreme insulin resistance. - Taylor, S I (1983)
Previously, we have described a novel qualitative defect in insulin receptors from a patient with a genetic form of extreme insulin resistance (leprechaunism). Receptors from this insulin-resistant child are characterized by two abnormalities: (a) an abnormally high binding affinity for insulin, and (b) a markedly reduced sensitivity of 125I-insulin binding to alterations in pH and temperature. In this paper, we have investigated the kinetic mechanism of this abnormality in steady-state binding. The increased binding affinity for 125I-insulin results from a decrease in the dissociation rate of the hormone-receptor complex. In addition, the cooperative interactions among insulin binding sites are defective with insulin receptors from this child with leprechaunism. With insulin receptors on cultured lymphocytes from normal subjects, both negative and positive cooperativity may be observed. Porcine insulin accelerates the dissociation of the hormone-receptor complex (negative cooperativity). In contrast, certain insulin analogs such as desoctapeptide-insulin and desalanine-desasparagine-insulin retard the dissociation of the hormone-receptor complex (positive cooperativity). With insulin receptors from the leprechaun child, positive cooperativity could not be demonstrated, although negative cooperativity appeared to be normal. It seems likely that the same genetic defect may be responsible for the abnormalities in both insulin sensitivity and positive cooperativity.